Evidence for Resilience Livestock (ERL): Livestock Feed Nutritional Metea-dataset from Africa - Steward, Peter Richard; Joshi, Namita; Rosenstock, Todd Stuart (2025)
Purpose, Nature, and Scope: This data collection focuses on extracting and organizing data on animal feed nutritional composition and digestibility as part of the Evidence for Resilient Agriculture (ERA) initiative. The dataset serves as a foundational resource for understanding livestock feed practices and their implications for productivity, sustainability, and environmental impact. While no specific research questions have been addressed yet, the dataset provides a critical input for ongoing and future research. Special Characteristics: The dataset includes: • Nutritional composition data (e.g., protein, fiber, and energy content) for various feed types. • Digestibility data (e.g., dry matter and energy digestibility) relevant to livestock systems. • Contextual metadata, such as livestock species, feed types, and geographic locations. The data is curated within the ERA data model, using a controlled vocabulary for consistency and interoperability. Applications: This dataset can be shared with collaborators who have developed emissions calculators requiring detailed information about the nutritional composition and digestibility of livestock diets. These tools use such data to estimate emissions and develop mitigation strategies by analyzing or modifying animal diets.